The Discourse Structure and Linguistic Features of Research Articles and Thesis Abstracts in English by Indonesian Academics - Alek, Alek; Marzuki, Abdul Gafur; Hidayat, Didin Nuruddin; Fauzji, Fahmi (Journal of Education, Language Innovation, and Applied Linguistics, 2022)
Scholars and practitioners should be aware that writing a good and eye-catching abstract is significant but tough work. Scholars and researchers are challenged to produce an informative and persuasive abstract to be accepted then published in either national or international publication and they should know the current characteristics of abstracts written by the students or apprentice writers. The study aims at examining the comparison of discourse structure and linguistic features between English abstracts of research articles by Indonesian researchers and English abstracts of the thesis by Indonesian scholars. The corpus data were taken from 10 research articles abstracts of Indonesian researchers concerning English education published in ERIC and 10 thesis abstracts of the graduate program of English Education in UIN Syarif Hidayatullah Jakarta. Thus, a genre-based analysis proposed by Bhatia’s move structure and Swales’ and Feak’s move structure will be used to investigate the discourse structure and Paltridge starfields will be used to investigate linguistic features. The results indicated that 60% of abstracts published in the international journal were organized well while 40% of thesis abstracts were not organized well. Furthermore, past tenses were frequently used in both article abstracts and thesis abstracts in terms of aim, method, and result move. While present tense was still used in aim and result move in article abstracts. In conclusion, most abstracts published in international publications used well organizational move. While most abstracts published in local ones are not used well organizational move.Keywords: Discourse structure; linguistic features; research article abstracts; rhetorical move; thesis abstracts.